A review on Simulate Fracture and Ultra-Low Cycle Fatigue in Steel Structures by ABAQUS (Journal of Civil Engineering Researchers, 2023)
In recent years, many advances have been made in fatigue and failure modeling in steel structures. The methods used to simulate failure and fatigue caused by earthquakes in steel structures are based on experimental and semi-empirical methods or conventional fracture mechanics. Semi-empirical methods cannot be generalized to a wide range of structural details, but conventional fracture mechanics can be reliably used only to simulate brittle fractures such as those observed in the Northridge and Kobe earthquakes, where large-scale yielding is absent. Similar to what is described in this paper, physics-based micromodels seek to simulate the fundamental processes of void growth and coalescence and granular shear responsible for very low-cycle fracture and fatigue in structures. These models are relatively free of assumptions about behavior and can be accurately used to simulate fracture and fatigue in a general sense under different conditions. The growth of voids or cracks can cause sudden crack propagation and deterioration of strength on a global scale of structural components. Therefore, these micromodels, relying on fundamental physics, are equally applicable to situations considered as "brittle" or "unbreakable" at the structural or component level. Examples are given to demonstrate the use of one of these models - the Cyclic Void Growth Model (CVGM) - to simulate failure through continuous finite element analyses.
Keywords: crack; fracture energy; low cyclic; fatigue; steel structure